1995
DOI: 10.1002/cyto.990200112
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative cytofluorimetric determination of cell membrane‐associated large tumor antigen on SV40‐transformed cells

Abstract: The aim of this study was to quantitate the number of cell membrane-located SV40 large tumor antigen (large T) molecules of SV40-transformed cell lines by cytofluorimetric analysis. Five different SV40-transformed cell lines were labelled by either a biotin-or a fluorescein-conjugated monoclonal antibody, PAb1605, which is specmc for the large T carboxyterminus. The conjugated-antibody fluorescence signals of the stained large T molecules of transformed cells were measured via cytofluorimetry. Comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For the intracellular estrogen receptor, variability was higher (r ϭ 0.63) (25). Several studies have utilized this approach for surface antigens (33)(34)(35) and intracellular antigens (36) without verifying the assumptions. Given the uncertainties in this antibody-bead technology and the difficulty of independent verification for proteins that do not bind radiolabeled ligands, the data for these studies are less easily accepted in terms of molecular quantification than they are in terms of standardization.…”
Section: Other Approachesmentioning
confidence: 95%
“…For the intracellular estrogen receptor, variability was higher (r ϭ 0.63) (25). Several studies have utilized this approach for surface antigens (33)(34)(35) and intracellular antigens (36) without verifying the assumptions. Given the uncertainties in this antibody-bead technology and the difficulty of independent verification for proteins that do not bind radiolabeled ligands, the data for these studies are less easily accepted in terms of molecular quantification than they are in terms of standardization.…”
Section: Other Approachesmentioning
confidence: 95%
“…Variable expression of SV40 large T antigen in transgenic mouse tumor models (Wikenheiser et al, 1992) and transformed cell lines (Hess et al, 1995) has been reported. To test the reliability of large T antigen expression, MFLM-91U were used to form tumors following subcutaneous injection in nude mice.…”
Section: Mflm Cells Chimerize Vascular Structures In Vivomentioning
confidence: 95%